Posisi Agama dalam Konstruksi Negara Republik Indonesia Berdasarkan Pancasila dan UUD 1945 - Sukirno, Sukirno (Jurnal Hukum Caraka Justitia, 2021)
This paper discusses the position of religion and the implementation of its teachings in the construction of the Republic of Indonesia based on Pancasila and the 1945 Constitution. Pancasila as the fundamental basis for the Republic of Indonesia makes the principle of 'Ketuhanan Yang Maha Esa' or translated as 'belief in the one and only God' as the main basis that animates the other four principles. As a consequence, the Republic of Indonesia must accept and put the values of the belief in the one and only God which is expressed in religious teachings, in all activities of the society, both in the private and in the public-country domain.In the private sphere, the state guarantees and protects citizens to embrace religion and worship based on religious teachings and beliefs. In the public sphere, the country gives an important religious position by placing religious values as the material source of all positive legal rules and as the ethical and moral foundation in the life of the nation and country hood. Also, the country must accommodate openly, freely, fairly, and in balance with religious-patterned aspirations to take part in country politics through social organizations and political parties. Religion does not integrate (fusion) into the country, but also the country does not separate from religion.